2011
DOI: 10.1007/s11130-011-0233-5
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution and Elimination of Carnosic Acid, A Natural Antioxidant from Rosmarinus officinalis, in Rats

Abstract: The absorption, distribution and elimination of carnosic acid, the main antioxidant found in rosemary was studied, in vivo, in rats. Therefore, carnosic acid was administrated in a single dose, intravenously (20.5 ± 4.2 mg/kg) and orally (64.3 ± 5.8 mg/kg), to four and nine rats, respectively. Blood samples were collected at different time points, and plasma concentrations of carnosic acid were determined using LC-MS. Furthermore, total collection of urine and feces was done during 4 h and 24 h for the intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 21 publications
4
38
1
Order By: Relevance
“…The rosemary extract study utilized female Zucker rats, while the pure carnosic acid studies utilized Sprague-Dawley males. One apparent advantage of rosemary diterpenes such as carnosic acid is the high bioavailability with estimates ranging from 40 to 65% which is significantly higher than other phytochemicals which could be as low as 1 to 5% [68,69,73,74].Taken together, the pharmacokinetic profile of carnosic acid appears to be well within the concentrations that have been used to report a variety of pharmacological actions in different cell culture models.…”
Section: Pharmacokineticsmentioning
confidence: 80%
See 1 more Smart Citation
“…The rosemary extract study utilized female Zucker rats, while the pure carnosic acid studies utilized Sprague-Dawley males. One apparent advantage of rosemary diterpenes such as carnosic acid is the high bioavailability with estimates ranging from 40 to 65% which is significantly higher than other phytochemicals which could be as low as 1 to 5% [68,69,73,74].Taken together, the pharmacokinetic profile of carnosic acid appears to be well within the concentrations that have been used to report a variety of pharmacological actions in different cell culture models.…”
Section: Pharmacokineticsmentioning
confidence: 80%
“…Oral administration of carnosic acid had the following parameters: time of maximum concentration (T max ) (125.6min), maximum plasma concentration (C max ) (126μM), area under the curve (AUC 0-t ) (21755.3mg/L/min), and oral bioavailability (65.09%). A second study with male SpragueDawley rats (200-330g) administered carnosic acid intragastrically (64.3mg/kg) achieving the following pharmacokinetic parameters: T max (136.6min), C max (105μM), AUC 0-t (7.05mg/mL/min), and oral bioavailability (40.1%) [69]. A third pharmacokinetic evaluation was performed using a rosemary extract standardized to 40% carnosic acid [70].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Therefore, at concentrations used as a food additive, it is assumed that carnosic acid levels would not cause significant hepatotoxicity or DDI. However, at doses needed to elicit statistically significant weight loss and antiadipogenic effects in ob/ob mice (Wang et al, 2011), it is calculated that plasma concentrations in these animals would exceed 100 M based on the published pharmacokinetic parameters of carnosic acid in the rat (Yan et al, 2009;Doolaege et al, 2011). This concentration is equal to or greater than the carnosic acid concentrations used in the current human hepatocyte studies.…”
Section: Discussionmentioning
confidence: 98%
“…Metabolites were detected as early as 25 min after oral administration and most of the compounds remained present at substantial concentrations (micromolar range) for several hours [115]. Doolaege, et al reported that 64.3 mg/kg (193.43 mM) CA orally administered to rats resulted in a plasma concentration of 0.015 mg/mL (45.12 μM) [116]. Another study reported that ingestion of 360 mg/kg/day RA after 8 weeks resulted in a plasma concentration of 1.1 μM [117].…”
Section: Dosage and Bioavailabilitymentioning
confidence: 99%